Evaluasi dan perbandingan teknik elisitasi kebutuhan dalam pengembangan perangkat lunak context-aware - Saputra, Dimas Arya; Hendrawan, Muhammad Reyhan Aditya; Zidannizar, Muhammad Putra; Yaqin, Muhammad Ainul (Maliki Interdisciplinary Journal, 2024)
This paper aims to evaluate and compare several requirements elicitation methods in the development of context-aware software. The authors emphasize the importance of considering context in software development and discuss various techniques for gathering requirements while taking context into account. The evaluated methods include interviews, observations, and surveys. In this article, the authors use the evaluation results to compare and contrast the most effective and efficient methods for obtaining high-quality requirements. The evaluation results indicate that the use of a combination of interview and survey methods can yield better results compared to relying on a single method. The authors also highlight some challenges in context-related requirements elicitation, such as the need to consider user privacy and collecting accurate data. In conclusion, the authors underscore the significance of considering context and adopting the appropriate approach in requirements elicitation for the development of context-aware software.